The Effort of Improving Grammar Mastery Through Wordwall Unjumble Sentence - Yudhawati, Haliza Tri; Iffah, Ida Farhatul; Putri, Intan Cahyani; Melyana, Mita; Almanar, Muhammad Abduh (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
Teaching grammar should be enjoyable to inspire students to achieve better results. Teachers need to recognize that today's students are digital natives who are adept at utilizing technology for learning enhancement. This research aims to explore how the use of the unjumble sentence feature on Wordwall can improve students’ grammar mastery. Classroom action research was employed in this study. The subjects of this research were five students, which consisted of two males and three females, aged between 13-15 years. The instruments used in this research were observation and test. After the implementation of Wordwall in Cycle 1, The findings indicated that initially, 60% of students met the Minimum Criteria of Mastery in Cycle 1, which increased to 80% in Cycle 2. The findings demonstrate that Wordwall unjumble sentence significantly enhanced grammar mastery by making learning more interactive and engaging.